The use of non-human primates in biomedical research: addressing the replacement impasse through the social dynamics of science - Hudson-Shore, Michelle (2015)
Non-human primate experimentation provokes passionate and opposing exchanges, particularly in the UK. This disagreement contributes to an impasse which in turn has prevented the exploration of the important question, if and how primate research could be ended. This project aims to support the examination of this question of impasse presenting data on how it might be overcome by providing a novel and challenging perspective using a multi-method approach, and insights from science and technology studies, to better understand the animal research controversy.